Multi-Scalar Localization and Capability Transference: Exploring Embeddedness in the Asian Retail Expansion of Tesco. Issue 3 (3rd March 2016) - Wood, Steve; Coe, Neil M.; Wrigley, Neil
Abstract : Wood S., Coe N. M. and Wrigley N. Multi-scalar localization and capability transference: exploring embeddedness in the Asian retail expansion of Tesco, Regional Studies . This paper revisits the 'firm in the region' and the 'region in the firm' dichotomy through the case of Tesco's retail expansion in Asia. It focuses on the tension between the transference of proven key capabilities to the host economies Tesco has entered, and strategic localization, primarily for customer-facing, corporate culture, regulatory and institutional reasons. It is demonstrated how the retailer has pursued a multi-scalar adaptive approach that goes beyond any standardized/localized dichotomy to respond to differences between and within national markets. In the process, this paper provides evidence of genuine two-way knowledge flow between the home market and subsidiaries, between subsidiaries themselves, and of subsidiaries granted autonomy and the ability to flex their strategies.